Analysis of Grounding System Resistance Value Changes at PT. Telekomunikasi Indonesia Tbk., Witel Cirebon - Mahadi (PT Pustaka Intelektual Sutajaya, 2025)
This study analyzed longitudinal changes in grounding resistance at nine Automatic Telephone Centers (STOs) in Cirebon, Indonesia, from July 2017 to January 2021. The objective was to determine whether grounding resistance values exceeded the national standard limit of 1 ohm and to identify environmental factors influencing their variation. Grounding resistance was measured biannually during dry and rainy seasons using standardized field methods. Descriptive statistics and paired t-tests were employed to assess trends and seasonal differences. The results showed that all STOs maintained resistance values within the acceptable threshold, with consistently lower values observed during the rainy season due to increased soil moisture. Seasonal differences in resistance were statistically significant, and additional influencing factors included soil composition, drainage area, and physical system conditions. The findings highlighted the critical role of environmental variability in grounding system performance and emphasized the importance of periodic monitoring to maintain system safety and reliability in tropical climates.